Klasifikasi Kegagalan Investasi Reksa Dana Sebagai Utang dalam Kasus Penundaan Kewajiban Pembayaran Utang Terhadap Manajer Investasi Dikaitkan dengan Dengan Undang-Undang Nomor 8 Tahun 1995 dan Undang- Undang Nomor 37 Tahun 2004 : (Studi Kasus Putusan Putusan Pn Jakarta Pusat Nomor 78/Pdt.Sus-PKPU/2020/PN Niaga Jkt.Pst) - Marla Satika Qurratu’aini; Nyulistiowati Suryanti; Sudaryat Sudaryat (Pusat Riset dan Inovasi Nasional, 2024)
Along with globalisation, economic development continues to change dynamically in order to achieve success in national economic development. National economic development is the development of equitable economic growth for the greatest prosperity of all Indonesian people based on the principle of kinship in accordance with Pancasila and the 1945 fourth amendment of the Republic of Indonesia. This economic development is marked by the development of a variety of transactions or economic activities, one of which is investment or capital activities through the capital market such as mutual fund investments made through the role of investment managers. In carrying out its business activities, there is a risk of default that can result in a Suspension of Payment against the Investment Manager, one of which is the case of Central Jakarta District Court Decision Number 78/Pdt.Sus-PKPU/2020/PN Niaga Jkt.Pst. This research aims to examine the accuracy of the consideration of the Central Jakarta District Court judge in the related decision regarding the qualification of investment losses as a default charged to the Investment Manager, as well as the judge's consideration in accepting the suspension of payment application against PT Emco as the Investment Manager by the Investor. This research uses the juridical-normative method, which prioritises the use of literature material from positive law as a source with the results of the research described descriptively. The results of this study show conclusion that can be drawn. The judge's consideration in the relevant decision is not correct because the responsibility for default should be borne by the issuer, in addition, the judge's consideration does not conduct further investigation regarding the origin of the compensation agreement between the Investment Manager and the Investor.